Preparation method and application of hydrophobic-gas permeable uiO-66 composite material

CN122974283APending Publication Date: 2026-10-27BEIJING INSTITUTE OF GRAPHIC COMMUNICATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610910950.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有技术中存在的不足,本发明目的是提供疏水-亲气的UiO-66复合材料的制备方法及其应用,以解决现有UiO-66气敏材料在湿度环境下因水分子竞争吸附导致目标气体吸附容量下降、选择性变差的技术问题,本发明方法通过构建疏水界面阻隔水蒸气,并优化UiO-66界面吸附结构,利用亲气界面吸附目标气体,使UiO-66复合材料兼具疏水性与气体亲和力双功能,在高湿环境下仍能保持优异的稳定性和气体吸附能力,可广泛适用于构建应用于高性能气体传感器、呼吸监测和环境监测等领域

Benefits of technology

(1)本发明通过分步改性的方法,将疏水官能团选择性地配位于UiO-66的外表面及孔道口区域,形成疏水屏障层,有效阻止水分子进入材料内部;同时在孔道内部引入对目标气体具有特异性识别能力的亲气功能位点,保留并增强了材料对目标气体的高亲和性吸附能力;疏水性能和亲气性能协同增强的空间分布结构,从根本上解决了现有改性技术中疏水和亲气难以兼顾的不足。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a kind of preparation methods and applications of hydrophobic-gas affinity UiO-66 composite material, belong to adsorbing material preparation and gas sensing technical field, the method of the present application is by constructing hydrophobic interface barrier water vapor, and optimization UiO-66 interface adsorption structure, using gas-sensitive interface adsorption target gas, make UiO-66 composite material have hydrophobicity and gas sensitivity dual function, still can keep excellent stability and sensitivity under high humidity environment, solve the technical problem that existing UiO-66 gas-sensitive material is in humidity environment due to water molecule competition adsorption and causes target gas adsorption capacity to decline, poor selectivity, can be widely applied to build and be applied to high-performance gas sensor, breath monitoring and environmental monitoring and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of adsorption material preparation and gas sensing technology, specifically to a method for preparing a hydrophobic-aerophilic UiO-66 composite material and its application. Background Technology

[0002] Metal-organic frameworks (MOFs) are a class of crystalline porous materials formed by the self-assembly of metal ions / clusters and organic ligands through coordination bonds. Due to their high specific surface area, abundant permanent pores, and tunable pore size structure, they are widely used in gas adsorption, catalysis, and sensing. UiO-66 (University of Oslo66) is a typical MOF material constructed from Zr6O4(OH)4 metal clusters and terephthalic acid ligands, exhibiting excellent thermal, chemical, and water stability. Compared with other MOFs, UiO-66 demonstrates superior structural stability under acidic / alkaline environments and water vapor conditions, thus being considered one of the most promising MOF materials for practical application.

[0003] However, in practical applications, the structure of UiO-series materials typically exhibits hydrophilicity. The pore surface of UiO-66 contains abundant hydroxyl groups and uncoordinated metal nodes; these polar sites possess high adsorption energies for polar water molecules. When ambient humidity is high, water molecules preferentially occupy the pores of UiO-66, competing with the target gas for adsorption, leading to a decrease in the material's effective adsorption capacity for the target gas. This problem is particularly prominent in applications requiring high selectivity, such as trace gas detection and low-concentration gas separation.

[0004] Existing technologies attempt to hydrophobically modify MOFs, such as by introducing hydrophobic ligands or coating them with hydrophobic polymers like polydimethylsiloxane, to improve the materials' waterproof performance. However, these methods all have shortcomings: First, functionalization: conventional modification methods only focus on hydrophobicity and improving the water contact angle, neglecting the interfacial affinity between the material and the gas. This results in modified MOFs materials being moisture-resistant but with significantly reduced gas adsorption capacity. Second, pore blockage: when using polymer coating to improve hydrophobicity, the polymer easily blocks the nanopores of MOFs, affecting their original specific surface area advantage. Third, interface control is difficult: existing chemical modification techniques struggle to achieve a synergistic effect of hydrophobicity and gas affinity at the same interface, and there are no mature synthesis methods, especially lacking design for interfacial affinity specific to certain gases.

[0005] Therefore, developing a method for preparing UiO-66 composite materials that can simultaneously enhance hydrophobic and aerophilic properties is of great significance for expanding the practical application of UiO-66 in humid environments. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing hydrophobic-aerophilic UiO-66 composite materials and their applications. This method solves the technical problem that existing UiO-66 gas-sensitive materials suffer from decreased adsorption capacity and poor selectivity of target gases due to competitive adsorption of water molecules in humid environments. The present invention constructs a hydrophobic interface to block water vapor and optimizes the adsorption structure of the UiO-66 interface, while utilizing the aerophilic interface to adsorb the target gas. This enables the UiO-66 composite material to possess both hydrophobicity and gas affinity, maintaining excellent stability and gas adsorption capacity even in high humidity environments. It can be widely applied to the construction of high-performance gas sensors, respiratory monitoring, and environmental monitoring.

[0007] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: This invention provides a method for preparing a hydrophobic-aerophilic UiO-66 composite material. The hydrophobic-aerophilic UiO-66 composite material is prepared by introducing hydrophobic functional groups on UiO-66 nanoparticles with a hydrophobic modifier to form a hydrophobic barrier layer; and by introducing aerophilic functional sites with specific recognition ability for target gases on UiO-66 nanoparticles with aerophilic organic ligands, thereby synergistically enhancing the hydrophobic and aerophilic properties of the UiO-66 composite material.

[0008] Preferably, the molar ratio of the hydrophobic modifier to the UiO-66 nanoparticles is 1:3.

[0009] Preferably, the molar ratio of the UiO-66 nanoparticles to the gas-loving organic ligand is 1:0.2 to 1:1.2.

[0010] Preferably, the gas-loving organic ligand is at least one of amino terephthalic acid, hydroxy terephthalic acid, carboxy terephthalic acid, and porphyrin ligands.

[0011] Preferably, the preparation method specifically includes the following steps: S1. Preparation of UiO-66 material: Zirconium source and organic ligand 1 were dissolved in organic solvent 1 at a molar ratio of 1:1 and then mixed. Modifier was added, and UiO-66 nanoparticles were synthesized by solvothermal method. After centrifugation, washing and drying, UiO-66 nanoparticles were obtained. S2. Construction of hydrophobic functional layer: The UiO-66 nanoparticles obtained in S1 are dispersed in organic solvent 2 or deionized water, and a hydrophobic modifier is added. The molar ratio of the hydrophobic modifier to the UiO-66 nanoparticles is 1:3. A hydrophobic modification reaction is carried out so that the hydrophobic functional groups are located on the outer surface and pore opening of the UiO-66 nanoparticles to form a hydrophobic barrier layer. The inside of the pores remains unmodified. The collected samples are washed with acetic acid and deionized water and dried to obtain hydrophobically modified UiO-66 nanoparticles. S3. Construction of gas-loving functional sites: The hydrophobic modified UiO-66 nanoparticles obtained in S2 were impregnated in a gas-loving organic ligand solvent at a molar ratio of 1:0.2 to 1:1.2. Through ligand exchange process, an organic ligand II with specific recognition ability for the target gas was introduced into the pores of the hydrophobic modified UiO-66 nanoparticles to form gas-loving functional sites. S4. The product obtained in S3 is centrifuged, washed, and dried to obtain the UiO-66 composite material with both hydrophobic and aerophilic functions.

[0012] Preferably, the hydrophobic modifier in S2 is at least one of octadecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, perfluorotetradecanoic acid, perfluorodecyltrimethoxysilane, stearic acid, and 4,4',4''-((((2,4,6-trimethylbenzene-1,3,5-triyl)tri(methylene))tri(oxy))tribenzoic acid (H3TBTC); The concentration of the hydrophobic modifier is 0.05-100 mmol; The hydrophobic modification reaction conditions are a temperature of 20℃ to 200℃ and a reaction time of 2 to 48 h.

[0013] Preferably, the organic ligand in S1 is terephthalic acid; The zirconium ion in S1 is selected from at least one of zirconium tetrachloride, zirconium oxide, and zirconium nitrate. The organic solvent in S1 is N,N-dimethylformamide; The organic solvent in S2 is one of acetic acid, ethanol, isopropanol, n-propanol, n-hexane, and toluene. The modifier in S1 is at least one of formic acid, acetic acid, hydrofluoric acid, hydrochloric acid, and benzoic acid.

[0014] Preferably, the target gas in S3 is at least one of carbon dioxide, methane, hydrogen, carbon monoxide, ammonia, chemical warfare agents, and volatile organic compounds.

[0015] The present invention also provides a hydrophobic-aerophilic UiO-66 composite material prepared by the preparation method described above.

[0016] The present invention also provides the application of the hydrophobic-aerophilic UiO-66 composite material prepared by the preparation method described above in gas sensors, respiratory monitoring, or environmental monitoring.

[0017] The beneficial effects of this invention are: (1) The present invention selectively locates hydrophobic functional groups on the outer surface and pore opening region of UiO-66 through a stepwise modification method to form a hydrophobic barrier layer, which effectively prevents water molecules from entering the interior of the material; at the same time, it introduces aerophilic functional sites with specific recognition ability for target gases into the pores, retaining and enhancing the high affinity adsorption capacity of the material for target gases; the spatial distribution structure that synergistically enhances hydrophobic and aerophilic properties fundamentally solves the shortcomings of existing modification technologies that make it difficult to balance hydrophobicity and aerophilicity.

[0018] (2) In an environment with a relative humidity of up to 60%, the composite material of the present invention has a 20-50% higher dynamic adsorption capacity for the target gas than the unmodified UiO-66, a 10-30% lower adsorption capacity for water vapor, and a 10-30% higher gas selectivity.

[0019] (3) In this invention, hydrophobic modification is applied only to the outer surface of the material and the pore opening, and the thickness of the modified layer is 30 nm-200 nm, without causing blockage in the pores; at the same time, by precisely controlling the concentration of the hydrophobic modifier and the reaction conditions, excessive closure of the pore opening is avoided, ensuring the rapid diffusion of the target gas molecules.

[0020] (4) The preparation method of the present invention does not require complex equipment, the reaction conditions are mild (atmospheric pressure, 20-200℃), and it is highly compatible with the synthesis and post-processing of existing MOF materials. It can be mass-produced and has good prospects for industrial application.

[0021] (5) The UiO-66 composite material prepared in this invention maintains the excellent thermal and water stability of UiO-66. The introduction of hydrophobic functional groups in the outer layer further enhances the hydrolysis resistance of the material. According to the stability test, after the composite material is placed at 100°C and 60% humidity for 7 days, its structural integrity and adsorption performance retention rate exceeds 80%.

[0022] (6) According to the detection or separation requirements of different target gases, the present invention can select the corresponding second organic ligand to construct specific gas-loving functional sites inside the pores. The composite material can be widely used in the fields of: adsorption of volatile organic compounds (VOCs) in high humidity environment, selective separation of low concentration of harmful gases in industrial production, and detection of disease markers in human exhaled gas. Attached Figure Description

[0023] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 Reflectance spectra of optical films made of pure UiO-66 material and optical films made of UiO-66 composite material prepared by the method of this invention, respectively, exposed to 60% water vapor. Figure 2 Reflectance spectra of optical films made of pure UiO-66 material and optical films made of UiO-66 composite material prepared by the method of this invention, respectively, exposed to 3 ppm of the target gas chlorobenzene (C6H5Cl). Figure 3 Reflectance spectra of optical films made of pure UiO-66 material and optical films made of UiO-66 composite materials prepared by the method of this invention, respectively, exposed to 75% water vapor. Figure 4 The reflectance spectra of optical films made of pure UiO-66 material and optical films made of UiO-66 composite materials prepared by the method of this invention were exposed to 2.5 ppm of the target gas hydrogen chloride (HCl). Figure 5 Reflectance spectra of optical films made of pure UiO-66 material and optical films made of UiO-66 composite materials prepared by the method of this invention, respectively, exposed to 80% water vapor. Figure 6 Optical films made of pure UiO-66 material and optical films made of UiO-66 composite material prepared by the method of this invention were exposed to the reflectance spectra of 2 ppm target gas dimethyl methyl phosphate (DMMP). Detailed Implementation The preferred embodiments of the present invention will be described below with reference to the accompanying drawings. It should be understood that the following embodiments are given for illustrative purposes only and are not intended to limit the scope of the present invention. Those skilled in the art can make various modifications and substitutions to the present invention without departing from its spirit and essence.

[0024] This invention provides a method for preparing a hydrophobic-aerophilic UiO-66 composite material and its application. The method includes the following steps: S1. Preparation of UiO-66 material: Zirconium metal ions and organic ligand 1 were dissolved in organic solvent 1 at a molar ratio of 1:1 and then mixed. Modifier was added, and the molar ratio of modifier to zirconium metal ions was 140:1. UiO-66 nanoparticles were synthesized by solvothermal method. After centrifugation, washing and drying, UiO-66 nanoparticles were obtained. S2. Construction of hydrophobic functional layer: The UiO-66 nanoparticles obtained in S1 were dispersed in organic solvent II, a hydrophobic modifier was added, and after thorough stirring, the mixture was allowed to stand to carry out a hydrophobic modification reaction, so that the hydrophobic functional groups were located on the outer surface and pores of the UiO-66 nanoparticles, thus obtaining hydrophobically modified UiO-66 nanoparticles. The collected samples were washed with acetic acid and deionized water and dried for 24 hours; the molar ratio of the hydrophobic modifier to the UiO-66 nanoparticles was 1:3. S3. Construction of gas-loving functional sites: The hydrophobic modified UiO-66 nanoparticles obtained in S2 were impregnated in an organic ligand 2 solvent. Through a ligand exchange process, an organic ligand 2 with specific recognition ability for the target gas was introduced into the UiO-66 channels to form gas-loving functional sites; the molar ratio of the hydrophobic modified UiO-66 nanoparticles to the organic ligand 2 was 1:0.2 to 1:1.2. S4. The product obtained in S3 is centrifuged, washed, and dried to obtain the UiO-66 composite material with both hydrophobic and aerophilic functions.

[0025] The above steps involve first constructing hydrophobic functional sites and then constructing hydrophilic functional sites, or alternatively, constructing hydrophilic functional sites first and then constructing hydrophobic functional sites.

[0026] The zirconium ion in S1 is selected from at least one of zirconium tetrachloride, zirconium oxide, and zirconium nitrate; the organic ligand is terephthalic acid; the organic solvent is selected from N,N-dimethylformamide; the modifier is selected from at least one of formic acid, acetic acid, hydrofluoric acid, hydrochloric acid, and benzoic acid; the solvothermal synthesis reaction temperature is 20℃~200℃, and the reaction time is 2~48 h.

[0027] The hydrophobic modifier in S2 is a carboxylic acid derivative, silane coupling agent, organic ligand, etc., with a hydrophobic functional group, such as at least one of octadecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, perfluorotetradecanoic acid, perfluorodecyltrimethoxysilane, stearic acid, and 4,4',4''-((((2,4,6-trimethylbenzene-1,3,5-triyl)tri(methylene))tri(oxy))tribenzoic acid (H3TBTC); the hydrophobic functional group is at least one of an alkyl chain, a fluoroalkyl chain, or a phenyl group.

[0028] The hydrophobic modification reaction conditions in S2 are: temperature 20℃~200℃, reaction time 2~48 h, and concentration of hydrophobic modifier 0.05-100 mmol.

[0029] The hydrophobic modification reaction in S2 is carried out in an organic solvent, which can be one of acetic acid, ethanol, isopropanol, n-propanol, n-hexane, toluene, or deionized water. During the hydrophobic modification reaction, the amount of hydrophobic modifier is controlled so that the hydrophobic functional groups are located on the outer surface and pore opening region of UiO-66, while the inside of the pore remains unmodified.

[0030] In S3, organic ligand 2 is a functionalized ligand with specific recognition ability for target gases. Organic ligand 2 is selected from at least one of amino terephthalic acid, hydroxy terephthalic acid, carboxy terephthalic acid, porphyrin ligands, etc., with a concentration of 1-200 mmol / L and an impregnation time of 2-72h. Target gases include carbon dioxide, methane, hydrogen, carbon monoxide, ammonia, chemical warfare agents (such as sarin and mustard gas), volatile organic compounds (VOCs), etc.

[0031] The specific process of ligand exchange or secondary growth in S3 is as follows: the hydrophobic modified UiO-66 nanoparticles obtained in S2 are placed in a solution containing organic ligand II at a molar ratio of 1:0.2 to 1:1.2, and heated and stirred at 20-200℃ for 0.5-24h, so that some organic ligand I is replaced by the second organic ligand, forming gas-loving functional sites in the pores.

[0032] In the UiO-66 composite material with both hydrophobic and aerophilic functions, the hydrophobic functional groups are mainly distributed on the outer surface and pore openings of the material, forming a hydrophobic barrier layer; the aerophilic functional sites are distributed inside the pores, forming aerophilic functional sites. The hydrophobic principle is based on the fact that the hydrophobic functional groups, such as perfluorosilanes or H3TBTC groups in the aforementioned hydrophobic modifiers, have weak polarity and generally do not easily form hydrogen bonds with water molecules. Furthermore, they have lower surface energy than water, making it difficult for water droplets to spread, thus resulting in a larger water contact angle and exhibiting hydrophobicity. Gas molecules such as CO2 and CH4 are weakly polar or nonpolar, and are subject to relatively little resistance. The principle of gas affinity applies: specific functional groups play a major role. For example, if the target gas is CO2, it can be modified with functional groups such as amino (-NH2). Amino groups are Lewis bases, and the two can undergo coordination reactions to form carbamates. For gases such as CH4 and VOCs, physical adsorption generally occurs, with the gas being adsorbed through intermolecular van der Waals forces. For hydrogen, it can be modified with unsaturated metal sites, allowing the gas to adsorb onto the surface of transition metals. Therefore, the hydrophobic-gas affinity of the target gas, interface design, and the selection of functional groups are crucial.

[0033] The UiO-66 composite material with hydrophobic and oxyphilic dual functions obtained by the above preparation method has a core-shell spatial distribution structure: the outer layer is a region modified with hydrophobic functional groups with a thickness of 5-50 nm, and the inner layer is an unmodified UiO-66 skeleton or a UiO-66 skeleton containing oxyphilic functional sites.

[0034] Example 1 Preparation of S1.UiO-66 material: 35 mg zirconium chloride and 25 mg 1,4-phthalic acid (BDC) were dissolved in N,N-dimethylformamide (DMF) containing 0.5-2.0 mol / L acetic acid; the mixture was stirred with a magnetic stirrer and reacted at 120 °C for 12 h to synthesize UiO-66 nanoparticles via a solvothermal method; after cooling, the product was collected by centrifugation and washed multiple times with DMF, methanol, and deionized water; S2. Construction of the hydrophobic functional layer: To carry out the modification, 49 mg of hydrophobic modifier H3TBTC was dispersed in 4.9 ml of acetic acid, and the resulting solution was transferred to a polytetrafluoroethylene (PTFE) liner. Subsequently, the UiO-66 nanoparticle sample prepared in S1 was placed in the PTFE liner of the reactor at a molar ratio of hydrophobic modifier to UiO-66 nanoparticles of 1:3. After thorough stirring, the mixture was allowed to stand for hydrophobic modification reaction. The reactor was heated at 80 °C for 12 h. The collected sample was washed with acetic acid and deionized water and dried for 24 h to obtain hydrophobically modified UiO-66 nanoparticles. The hydrophobic functional groups were located on the outer surface and pore openings of the UiO-66 nanoparticles.

[0035] S3. Introduction of hydroxyl functional sites: The introduction of hydroxyl functional sites is achieved by post-synthetic modification. First, the hydrophobically modified UiO-66 nanoparticles obtained in S2 were pre-activated for 12 h. The gas-loving organic ligand di-2-aminoterephthalic acid was dissolved in DMF for 10 h and then sonicated to form a solution. Then, the hydrophobically modified UiO-66 nanoparticles obtained in S2 were impregnated in the organic ligand di-2-aminoterephthalic acid solvent at a molar ratio of 1:0.2 for 2 h. The reaction was stirred at 25-60℃ for 12 h to carry out ligand exchange, introducing the organic ligand di-2, which has the ability to specifically recognize the target gas, into the pores of the hydrophobically modified UiO-66 nanoparticles to form gas-loving functional sites. S4. Centrifuge the product obtained in S3, wash twice with DMF to remove unreacted residues, and then wash three times with anhydrous ethanol or methanol. Finally, place the product in a vacuum drying oven and dry at 80°C for 12 hours to obtain the UiO-66 composite material with hydrophobic and anaerobic functions.

[0036] The hydrophobicity and gas adsorption properties of the UiO-66 composite material with hydrophobic and gas-philic dual functions obtained in Example 1 were tested.

[0037] The gas detection principle is as follows: The response principle of optical thin films made of pure UiO-66 material and optical thin films made of UiO-66 composite materials prepared by the method of this invention is based on the reflection wavelength shift caused by the change in effective refractive index (neff) after the adsorption of gas molecules and water molecules. This can be explained by Bragg's law combined with Snell's law, as shown in the following formula: ; Where m is the diffraction order, λ is the incident wavelength, d is the distance between atoms in the crystal lattice, θ is the incident angle, and neff is the effective refractive index. The effective refractive index can be calculated using the following method: ; Where f is the volume fraction of the particles, nm is the refractive index of the medium, and np is the refractive index of the particles. In our tests, the incident angle θ is constant, and the entry of gas molecules will change neff, thus changing λ. Therefore, the optical response of the thin film can be represented by the reflection spectrum; the more guest molecules absorbed, the greater the neff of the optical thin film, and the greater the shift in the reflection wavelength.

[0038] like Figure 1 The figures show the reflectance spectra of films made from pure UiO-66 material and films made from the UiO-66 composite material prepared by the method of this invention, exposed to 60% water vapor. The baseline indicates no exposure to any gas. The green curve represents the film made from pure UiO-66 material, and the red curve represents the reflectance spectra of the film made from the UiO-66 composite material exposed to 60% water vapor. The results show that compared to pure UiO-66 material, the UiO-66 composite material has a smaller reflectance spectral shift, indicating that the UiO-66 composite material has a poorer response to water molecules and exhibits better hydrophobicity.

[0039] like Figure 2 The figures show the reflectance spectra of films made from pure UiO-66 material and films made from the UiO-66 composite material prepared by the method of this invention, exposed to 3 ppm of the target gas chlorobenzene (C6H5Cl). The baseline indicates no exposure to any gas. The blue curve represents the film made from pure UiO-66 material, and the black curve represents the reflectance spectra of the film made from the UiO-66 composite material exposed to 3 ppm of the target gas chlorobenzene (C6H5Cl). The results show that, compared with pure UiO-66 material, the UiO-66 composite material exhibits a larger reflectance spectral shift in response to C6H5Cl, indicating that the UiO-66 composite material has improved adsorption performance for chlorobenzene and is more sensitive to gases.

[0040] according to Figure 1 and Figure 2 The test results show that the UiO-66 composite material is more hydrophobic and more air-loving.

[0041] Example 2 Preparation of S1.UiO-66 material: 35 mg zirconium chloride and 25 mg 1,4-phthalic acid (BDC) were dissolved in N,N-dimethylformamide (DMF) containing 0.5-2.0 mol / L acetic acid; the mixture was stirred with a magnetic stirrer and reacted at 120 °C for 12 h to synthesize UiO-66 nanoparticles via a solvothermal method; after cooling, the product was collected by centrifugation and washed multiple times with DMF, methanol, and water; S2. Construction of the hydrophobic functional layer: To carry out the modification, 49 mg of the hydrophobic modifier H3TBTC was dispersed in 4.9 ml of ethanol, and the resulting solution was transferred to a polytetrafluoroethylene (PTFE) liner. Subsequently, the UiO-66 nanoparticle sample prepared in S1 was placed in the PTFE liner of the reactor at a molar ratio of hydrophobic modifier to UiO-66 nanoparticles of 1:3. After thorough stirring, the mixture was allowed to stand for hydrophobic modification reaction. The reactor was heated at 80 °C for 12 h. The collected sample was washed with acetic acid and deionized water and dried for 24 h to obtain hydrophobically modified UiO-66 nanoparticles. The hydrophobic functional groups were located on the outer surface and pore openings of the UiO-66 nanoparticles.

[0042] S3. Introduction of hydroxyl functional sites: The introduction of hydroxyl functional sites is achieved by post-synthetic modification. First, the hydrophobically modified UiO-66 nanoparticles obtained in S2 were pre-activated for 12 h. The gas-loving organic ligand dihydroxyterephthalic acid was dissolved in DMF for 10 h and then sonicated to form a solution. Then, the hydrophobically modified UiO-66 nanoparticles obtained in S2 were impregnated in the organic ligand dihydroxyterephthalic acid solvent at a molar ratio of 1:0.8 for 2 h. The reaction was stirred at 25-60℃ for 12 h to carry out ligand exchange, introducing an organic ligand II with specific recognition ability for the target gas into the pores of the hydrophobically modified UiO-66 nanoparticles to form gas-loving functional sites. S4. Centrifuge the product obtained in S3, wash twice with DMF to remove unreacted residues, and then wash three times with anhydrous ethanol or methanol. Finally, place the product in a vacuum drying oven and dry at 80°C for 12 hours to obtain the UiO-66 composite material with hydrophobic and anaerobic functions.

[0043] The hydrophobicity and gas adsorption properties of the UiO-66 composite material with hydrophobic and aerophilic dual functions obtained in Example 2 were tested, and the results showed that: like Figure 3As shown, the reflectance spectra of films made from pure UiO-66 material and films made from the UiO-66 composite material prepared by the method of this invention are exposed to 75% water vapor. The baseline indicates no exposure to any gas. The blue curve represents the film made from pure UiO-66 material, and the red curve represents the reflectance spectra of the film made from the UiO-66 composite material exposed to 75% water vapor. The results show that compared to pure UiO-66 material, the UiO-66 composite material has a smaller reflectance spectral shift, indicating that the UiO-66 composite material has a worse response to water molecules and better moisture resistance. Compared to... Figure 1 The reflectance spectrum under 60% water vapor was measured. When the humidity increased to 75%, the reflectance spectral shift of the UiO-66 composite material was still smaller than that of the pure UiO-66 material, indicating that even with increased humidity, the UiO-66 composite material still has excellent moisture resistance.

[0044] like Figure 4 The figures show the reflectance spectra of films made from pure UiO-66 material and films made from the UiO-66 composite material prepared by the method of this invention, exposed to 2.5 ppm of the target gas hydrogen chloride (HCl). The baseline refers to films not exposed to any gas. The red curve represents the film made from pure UiO-66 material, and the blue curve represents the reflectance spectra of the film made from the UiO-66 composite material exposed to 2.5 ppm of the target gas hydrogen chloride (HCl). The results show that the reflectance spectral shift of the UiO-66 composite material is greater than that of pure UiO-66 material, indicating that even with a reduced gas concentration, the adsorption performance of the UiO-66 composite material for HCl is stronger than that of pure UiO-66 material, and it is more sensitive to gases.

[0045] Example 3 Preparation of S1.UiO-66 material: 35 mg zirconium chloride and 25 mg 1,4-phthalic acid (BDC) were dissolved in N,N-dimethylformamide (DMF) containing 0.5-2.0 mol / L acetic acid; the mixture was stirred with a magnetic stirrer and reacted at 120 °C for 12 h to synthesize UiO-66 nanoparticles via a solvothermal method; after cooling, the product was collected by centrifugation and washed multiple times with DMF, methanol, and water; S2. Construction of the hydrophobic functional layer: To carry out the modification, 49 mg of hydrophobic modifier H3TBTC was dispersed in 4.9 ml of deionized water, and the resulting solution was transferred to a polytetrafluoroethylene (PTFE) liner. Subsequently, the UiO-66 nanoparticle sample prepared in S1 was placed in the PTFE liner of the reactor at a molar ratio of hydrophobic modifier to UiO-66 nanoparticles of 1:3. After thorough stirring, the mixture was allowed to stand for hydrophobic modification reaction. The reactor was heated at 80 °C for 12 h. The collected sample was washed with acetic acid and deionized water and dried for 24 h to obtain hydrophobically modified UiO-66 nanoparticles. The hydrophobic functional groups were located on the outer surface and pore openings of the UiO-66 nanoparticles.

[0046] S3. Introduction of hydroxyl functional sites: The introduction of hydroxyl functional sites is achieved by post-synthetic modification. First, the hydrophobically modified UiO-66 nanoparticles obtained in S2 were pre-activated for 12 h. The gas-loving organic ligand dicarboxylic terephthalic acid was dissolved in DMF for 10 h and then sonicated to form a solution. Then, the hydrophobically modified UiO-66 nanoparticles obtained in S2 were impregnated in the organic ligand dicarboxylic terephthalic acid solvent at a molar ratio of 1:1.2 for 2 h. The reaction was stirred at 25-60℃ for 12 h to carry out ligand exchange. Organic ligand II with specific recognition ability for target gas was introduced into the pores of the hydrophobically modified UiO-66 nanoparticles to form gas-loving functional sites. S4. Centrifuge the product obtained in S3, wash twice with DMF to remove unreacted residues, and then wash three times with anhydrous ethanol or methanol. Finally, place the product in a vacuum drying oven and dry at 80°C for 12 hours to obtain the UiO-66 composite material with hydrophobic and anaerobic functions.

[0047] The hydrophobicity and gas adsorption properties of the UiO-66 composite material with hydrophobic and aerophilic dual functions obtained in Example 3 were tested, and the results showed that: like Figure 5 As shown, the reflectance spectra of films made from pure UiO-66 material and films made from the UiO-66 composite material prepared by the method of this invention are exposed to 80% water vapor. The baseline indicates no exposure to any gas. The blue curve represents the film made from pure UiO-66 material, and the red curve represents the reflectance spectra of the film made from the UiO-66 composite material exposed to 80% water vapor. The results show that compared to pure UiO-66 material, the UiO-66 composite material has a smaller reflectance spectral shift, indicating that the UiO-66 composite material has a worse response to water molecules and better moisture resistance. Compared to... Figure 1 , Figure 3The reflection spectra under 60% and 75% water vapor were measured. When the humidity increased to 80%, the reflection spectral shift of the UiO-66 composite material was still smaller than that of the pure UiO-66 material, indicating that even under ultra-high humidity conditions, the moisture resistance of the composite material remained at its best.

[0048] like Figure 6 The figures show the reflectance spectra of films made from pure UiO-66 material and films made from the UiO-66 composite material prepared by the method of this invention, exposed to 5 ppm of the target gas dimethyl methylphosphonate (DMMP). The baseline indicates no exposure to any gas. The red curve represents the film made from pure UiO-66 material, and the blue curve represents the reflectance spectra of the film made from the UiO-66 composite material exposed to 5 ppm of the target gas dimethyl methylphosphonate (DMMP). The results show that compared to pure UiO-66 material, the UiO-66 composite material exhibits a larger reflectance spectral shift, indicating that the UiO-66 composite material is more sensitive and has a stronger affinity for DMMP.

[0049] In summary, this invention selectively locates hydrophobic functional groups on the outer surface and pore opening region of UiO-66 material through a stepwise modification method, forming a hydrophobic barrier layer that effectively prevents water molecules from entering the material. At the same time, it introduces aerophilic functional sites with specific recognition capabilities for target gases into the pores, preserving and enhancing the material's high affinity adsorption capacity for target gases. Thus, a UiO-66 composite material with synergistic enhancement of hydrophobic and aerophilic properties is obtained.

[0050] The contents not described in detail in this specification are existing technologies known to those skilled in the art.

[0051] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic-aerophilic UiO-66 composite material, characterized in that, The hydrophobic-aerophilic UiO-66 composite material is prepared by introducing hydrophobic functional groups on UiO-66 nanoparticles with a hydrophobic modifier to form a hydrophobic barrier layer; and by introducing aerophilic functional sites with specific recognition ability for target gases on UiO-66 nanoparticles with aerophilic organic ligands, thereby synergistically enhancing the hydrophobic and aerophilic properties of the UiO-66 composite material.

2. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 1, characterized in that, The molar ratio of the hydrophobic modifier to the UiO-66 nanoparticles is 1:

3.

3. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 1, characterized in that, The molar ratio of the UiO-66 nanoparticles to the gas-loving organic ligand is 1:0.2 to 1:1.

2.

4. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 1, characterized in that, The gas-loving organic ligand is at least one of amino terephthalic acid, hydroxy terephthalic acid, carboxy terephthalic acid, and porphyrin ligands.

5. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 1, characterized in that, The preparation method specifically includes the following steps: S1. Preparation of UiO-66 material: Zirconium source and organic ligand 1 were dissolved in organic solvent 1 at a molar ratio of 1:1 and then mixed. Modifier was added, and UiO-66 nanoparticles were synthesized by solvothermal method. After centrifugation, washing and drying, UiO-66 nanoparticles were obtained. S2. Construction of hydrophobic functional layer: The UiO-66 nanoparticles obtained in S1 are dispersed in organic solvent 2 or deionized water, and a hydrophobic modifier is added. The molar ratio of the hydrophobic modifier to the UiO-66 nanoparticles is 1:

3. A hydrophobic modification reaction is carried out so that the hydrophobic functional groups are located on the outer surface and pore opening of the UiO-66 nanoparticles to form a hydrophobic barrier layer. The inside of the pores remains unmodified. The collected samples are washed with acetic acid and deionized water and dried to obtain hydrophobically modified UiO-66 nanoparticles. S3. Construction of gas-loving functional sites: The hydrophobic modified UiO-66 nanoparticles obtained in S2 were impregnated in a gas-loving organic ligand solvent at a molar ratio of 1:0.2 to 1:1.

2. Through ligand exchange process, an organic ligand II with specific recognition ability for the target gas was introduced into the pores of the hydrophobic modified UiO-66 nanoparticles to form gas-loving functional sites. S4. The product obtained in S3 is centrifuged, washed, and dried to obtain the UiO-66 composite material with both hydrophobic and aerophilic functions.

6. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 5, characterized in that, The hydrophobic modifier is at least one of octadecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, perfluorotetradecanoic acid, perfluorodecyltrimethoxysilane, stearic acid, and 4,4',4''-((((2,4,6-trimethylphenyl-1,3,5-triyl)tri(methylene))tri(oxy))tribenzoic acid (H3TBTC); The concentration of the hydrophobic modifier is 0.05-100 mmol; The hydrophobic modification reaction conditions are a temperature of 20℃ to 200℃ and a reaction time of 2 to 48 h.

7. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 5, characterized in that, The organic ligand in S1 is terephthalic acid; The zirconium source in S1 is selected from at least one of zirconium tetrachloride, zirconium oxide, and zirconium nitrate. The organic solvent in S1 is N,N-dimethylformamide; The organic solvent in S2 is one of acetic acid, ethanol, isopropanol, n-propanol, n-hexane, and toluene. The modifier in S1 is at least one of formic acid, acetic acid, hydrofluoric acid, hydrochloric acid, and benzoic acid.

8. The method for preparing the hydrophobic-aerophilic UiO-66 composite material according to claim 5, characterized in that, The target gas in S3 is at least one of carbon dioxide, methane, hydrogen, carbon monoxide, ammonia, chemical warfare agents, and volatile organic compounds.

9. The hydrophobic-aerophilic UiO-66 composite material prepared by the preparation method according to any one of claims 1-8.

10. The application of the hydrophobic-aerophilic UiO-66 composite material prepared by the preparation method according to any one of claims 1-8 in gas sensors, respiratory monitoring, or environmental monitoring.